Análise da implementação do estoque gerenciado pelo vendedor (Vendor Managed Inventory - VMI) nas indústrias de produtos alimentícios - Shintate, Jéssica Mie [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The increasing competition in the market, in addition to its dynamism, the accelerated development of technologies, globalization and diversity of customer's expectations are changing the market's competition from independent companies' competitions to supply chains' (SC) competitions. For these reasons many companies are investing in strategic partnerships with external organizations, and the Supply Chain Management (SCM) has become essential for the industries planning, aiming to reduce the total cost over the SC and increase the level of customer service. Among the aspects addressed in SCM, inventory management is relevant when the whole SC is considered. Considering the existing strategies for inventory management, the Vendor Managed Inventory (VMI) is one of the strategies that has shown to have good performances. In this context, the objective of this research was to verify the state of art, regarding published articles about VMI during the period from 2006 to 2017 through techniques from Systematic Review of the Literature, including a bibliometric research and the analysis of co-citations.Therefore, it was possible to verify the relevance of the subject in the literature, and others relevant bibliometric data. Besides that, it was also possible to identify the main keywords used and the scientific gaps. Finally, considering one of the items identified in the scientific gaps, a case study was made to show that the results cited in the literature are confirmed in a food industry

O aumento da concorrência no mercado, em conjunto com o seu dinamismo, o desenvolvimento acelerado de tecnologias, a globalização e a expectativa diversificada do cliente estão alterando o tipo de competição de mercado, de competição entre empresas independentes para competição entre Supply Chains (SC). Por isso, muitas empresas estão investindo em parcerias estratégicas com instituições externas, e o Supply Chain Management (SCM) tem se tornado essencial para o planejamento das indústrias, com o intuito de reduzir os custos totais ao longo da SC e aumentar o nível de serviço ao cliente. Dentre os vários aspectos tratados pelo SCM, a gestão de estoques é um tema muito relevante, considerando toda a SC. Considerando as estratégias existentes para o gerenciamento de estoques, o Estoque Gerenciado pelo Vendedor (Vendor Managed Inventory - VMI) é uma das estratégias que têm apresentado bons resultados. Nesse contexto, o objetivo deste trabalho foi verificar o estado da arte, com relação aos artigos sobre VMI publicados entre 2006 e 2017 por meio de técnicas da Revisão Sistemática da Literatura, incluindo a análise bibliométrica e a análise de co-citações.Dessa forma, foi possível constatar a relevância do tema na literatura, e outras informações bibliográficas relevantes. Além disso, também foi possível identificar as principais palavras-chave utilizadas e as lacunas científicas. Por fim, considerando um dos itens identificados nas lacunas científicas, realizou-se um estudo de caso, com o intuito de mostrar que o resultado citado pela literatura realmente ocorre nas práticas das empresas do setor de alimentos
Analysis of the implementation of stock managed by seller (Vendor Managed Inventory - VMI) in the food products industries
Keywords: Controle de estoque; Logistica empresarial; Estoques; Inventory control